If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying (2x^{3}+ 3) = 0 Reorder the terms: (3 + 2x^{3}) = 0 Remove parenthesis around (3 + 2x^{3}) 3 + 2x^{3}= 0 Solving 3 + 2x^{3}= 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x^{3}= 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x^{3}= 0 + -3 2x^{3}= 0 + -3 Combine like terms: 0 + -3 = -3 2x^{3}= -3 Divide each side by '2'. x^{3}= -1.5 Simplifying x^{3}= -1.5 Reorder the terms: 1.5 + x^{3}= -1.5 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 1.5 + x^{3}= 0.0 The solution to this equation could not be determined.

| (x^2+3)(x^3+2x^2+3x+6)+(2x^3+3)= | | 10y^2+33y+20=0 | | y^3+8y^2+16y=0 | | x^2+4x-60=0 | | 14x^2-5x=0 | | (x^3+y^5)(x^3-y^5)= | | 5x^2+11x+1=0 | | y^2-16y-4= | | y=5x^2-3x+5 | | 7x-28=2x^2-8x-3x+12 | | y=x^2+5x | | y=x^2+2x | | x^7-5x^5+x^2-5=0 | | 15x^2-8x-7=0 | | X^2+6x-27=0 | | 3x^2-6x+12=0 | | (4x^3-6x^2+5)-(8x^2+3x-6)= | | 11x^2-2x+9=0 | | 4x(2x^2-6x-5)= | | 10x^2+5x+8=0 | | 9x^2+9x+8=0 | | 12x^2+5x+10=0 | | 9x^2+21x+12=0 | | -2x^2+4x+12=0 | | 3x^2+10x+8=0 | | -8x^2+8x-2=0 | | X^2-x-2=0 | | 3x^2+x-1=0 | | (8x^4+5x^3-5)-(5x^2-6x+4)= | | 2x^2+10x+12=0 | | (7m^8-5m^3+9m^2+5)+(9m^7+3m^3-4m)= | | X^2-5x-48=0 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions